Political discourse in a transitional society: between the scylla of anarchy and the charybdis of tyranny - Яковлев, Денис Вікторович; Яковлев, Денис Викторович; Yakovlev, Denys V.; Єременко, Олександр Михайлович; Єременко, О. М.; Еременко, Александр Михайлович; Yeremenko, Oleksandr M. (Львів : «Ліга-Прес», 2020)
Сучасний політичний дискурс в Україні визначається як "нецивільний". Визначено, що громадянське суспільство недостатньо впливає на формування політичного дискурсу. Утопії є основною загрозою політичному дискурсу перехідного суспільства. Вони мають сильний вплив на громадську думку і тому використовуються для здобуття влади. Утопії виражаються у формі анархії та авторитаризму. Утопії посилюються політичною пропагандою, яка транслюється олігархічними ЗМІ. Збройний конфлікт на Сході України та окупація Криму, конституційний процес, мовна політика, протидія політичній корупції тощо є одними з основних тем політичного дискурсу, що вимагають більшої активності громадянського суспільства як альтернативи „утопії” дискурсу олігархічних ЗМІ.

Современный политический дискурс в Украине определяется как «антигражданский». Определено, что гражданское общество недостаточно влияет на формирование политического дискурса. Утопии представляют собой серьезную угрозу политическому дискурсу переходного общества. Они имеют сильное влияние на общественное мнение и поэтому используются для получения власти. Утопии выражаются в форме анархии и авторитаризма. Утопии усугубляются политической пропагандой, что транслируется олигархическими СМИ. Вооруженный конфликт на Востоке Украины и оккупация Крыма, конституционный процесс, языковая политика, противодействие политической коррупции и т. д. входят в число основных тем политического дискурса, которые требуют большей активности гражданского общества как альтернативы «утопии» дискурса олигархических СМИ.

The current political discourse in Ukraine is defined as “uncivil”. It is determined that civil society does not sufficiently influence the formation of political discourse. Utopias are a major threat to the political discourse of a transitional society. They have a strong influence on public opinion and are therefore used to gain power. Utopias are expressed in the form of anarchy and authoritarianism. Utopias are exacerbated by political propaganda which is broadcast by the oligarchic mass media. The armed conflict in the East of Ukraine and the occupation of Crimea, constitutional process, language policy, counteraction to political corruption, etc. are among the main topics of political discourse that require the greater activity of civil society as an alternative to the “utopia” of the discourse of the oligarchic mass media.
Yakovlev D. V. Political discourse in a transitional society: between the scylla of anarchy and the charybdis of tyranny / D. V. Yakovlev, O. M. Yeremenko // The level of efficiency and the need for the influence of social sciences on the development of modern civilization : collective monograph / K. S. Brenzovych, Yu. O. Ostapets, M. M. Palinchak, M. I. Tsalan, etc. – Lviv-Toruń : Liha-Pres, 2020. – P. 74-93.
Keywords: „утопії” політичного дискурсу; перехідне суспільство; політична пропаганда; олігархічні ЗМІ; "утопии" политического дискурса; переходное общество; политическая пропаганда; олигархические СМИ; “utopias” of the political discourse; transitional society; political propaganda; oligarchic mass media; Research Subject Categories::SOCIAL SCIENCES